Plectraterpene, a new ursane-type triterpene ester and other steroids from the aerial parts of Plectranthus montanus - Amina,Musarat (2017)
ABSTRACT A new ursane-type triterpene ester, plectraterpene [3β-(decanoyloxy)-19-hydroxy-urs-12-ene] and four known steroidal compounds have been isolated from the aerial parts of Plectranthus montanus Benth. (syn. Plectranthus cylindraceus Hochst. ex Benth.), Lamiaceae. The known compounds were stigmasterol, sitosteryl ferulate, cholest-5-en-3-O-β-D-glucopyranoside and stigmasterol-3-O-β-D-glucopyranoside. Compounds plectraterpene, sitosteryl ferulate and stigmasterol-3-O-β-D-glucopyranoside are reported for the first time from this plant whereas compound cholest-5-en-3-O-β-D-glucopyranoside first time from the genus. The structures of these compounds were determined through spectral analysis, including extensive 2D NMR data as well as chemical methods and comparison with literature.